Alternatively spliced mini-exon B in PTPδ regulates excitatory synapses through cell-type-specific trans-synaptic PTPδ-IL1RAP interaction - Seoyeong Kim; Jae Jin Shin; Muwon Kang; Yeji Yang; Yi Sul Cho; Hyojung Paik; Jimin Kim; Yunho Yi; Suho Lee; Hei Yeun Koo; Jinwoong Bok; Yong Chul Bae; et al. (Nature Communications)
Abstract PTPδ, encoded by PTPRD, is implicated in various neurological, psychiatric, and neurodevelopmental disorders, but the underlying mechanisms remain unclear. PTPδ trans-synaptically interacts with multiple postsynaptic adhesion molecules, which involves its extracellular alternatively spliced mini-exons, meA and meB. While PTPδ-meA functions have been studied in vivo, PTPδ-meB has not been studied. Here, we report that, unlike homozygous PTPδ-meA-mutant mice, homozygous PTPδ-meB-mutant (Ptprd-meB –/– ) mice show markedly reduced early postnatal survival. Heterozygous Ptprd-meB +/– male mice show behavioral abnormalities and decreased excitatory synaptic density and transmission in dentate gyrus granule cells (DG-GCs). Proteomic analyses identify decreased postsynaptic density levels of IL1RAP, a known trans-synaptic partner of meB-containing PTPδ. Accordingly, IL1RAP-mutant mice show decreased excitatory synaptic transmission in DG-GCs. Ptprd-meB +/– DG interneurons with minimal IL1RAP expression show increased excitatory synaptic density and transmission. Therefore, PTPδ-meB is important for survival, synaptic, and behavioral phenotypes and regulates excitatory synapses in cell-type-specific and IL1RAP-dependent manners.